Motivational Factors and Constraint Analysis Regarding Commercial Production of Mateera (Citrulus lanatus) in Hot Arid Ecosystem (Indian Journal of Extension Education, 2010)
The present study was conducted in Bikaner district of western Rajasthan and motivational factors and constraints being faced by the farmers in growing Mateera (Citrulus lanatus) crop in hot arid ecosystem of Rajasthan were analyzed. The major motivational factors of farmers behind mateera production at commercial scale as observed during the survey were: substantial income from mateera seeds, good earning from fresh mateerafruits, very low water requirement of the crop, high seed germination capacity, high consumption of mature mateera as a dessert fruits, immature Mateera fruits (Loiya) a very good source of vegetable, long storage life of the mateerafruit, high demand of mateeraeds in the markets, mateera juice protects the body from hot winds (Loo) during summer season, mateera juice helps in removing kidney stones, mateera is a very important component of traditional mixed cropping system of the arid regions, mateera is most suited crop in arid environment, etc. Amongst the major constraints being faced by the farmers in mateera production at large scale were: scarcity of water, very low and erratic rainfall and occurrence of drought very frequently, lack of viable schemes and support system for Mateera growers, no standardized technique is available for value addition of mateera fruits, very deep and salty ground water, inadequate supply of electricity, poor marketing system and market intelligence, lack of knowledge and awareness amongst the farmers about improved technologies of mateera cultivation, etc.